Deep learning for crack-like object detection - Zhang, Kaige, 1987-; Cheng, Heng-Da (Boca Raton : CRC Press, Taylor & Francis Grooup, 2023)
"With the development of artificial intelligence (AI), the deep learning technique has achieved great success. However, using deep learning for high accurate crack localization is non-trivial. Based on deep learning, this book has solved a bunch of important issues existing in crack-like object detection, and finished a practical smart pavement surface inspection system. By introducing those method and the system, this book gives the reader an easy way to get into the computer vision and deep learning research area. In addition, this research performs a preliminary study about the future AI system, which provides a concept that has potential to realize fully automatic crack detection without human's intervention"--
Introduction. Crack Detection with Deep Classification Network. Crack Detection with Fully Convolutional Network. Crack Detection with Generative Adversarial Learning. Self-Supervised Structure Learning for Crack Detection. Deep Edge Computing. Conclusion and Discussion.
"A Science Publishers book."
OCLC-licensed vendor bibliographic record.
Keywords: COMPUTERS / Machine Theory; COMPUTERS / Computer Engineering; SCIENCE / Life Sciences / General; Pavements, Concrete -- Testing -- Data processing; Concrete -- Cracking; Deep learning (Machine learning)